BLOOD SMEAR PROFILE OF PATIENTS WITH DENGUE HEMORRHAGIC FEVER IN BALI ROYAL HOSPITAL - Adnyana, I Made Dwi Mertha; Sudaryati, Ni Luh Gede; Suardana, A.A Komang (Faculty of Vocational Studies, Universitas Airlangga, 2021)
Background: Each year, dengue hemorrhagic fever has grown. Clinical hematological examinations and blood preparations are used to confirm the diagnosis. Purpose: To detect, assess and characterize dengue hemorrhagic fever blood smear at Bali Royal Hospital. Method: Cross-sectional descriptive observational study-was conducted in April at Bali Royal Hospital on 37 patients with dengue hemorrhagic fever, clinical hematological tests and the manufacture of blood preparations identified using inclusion and exclusion criteria. Platelet counts, hemoglobin levels, hematocrit values, leukocyte counts, clinic degrees, gender and age, and blue plasma lymphocytes, are all used in hematological analyzed by univariate, ANOVA and BNT tests to analyze data. Result: Patients with dengue hemorrhagic fever are mostly toddlers and children (35.13%), women (54.0%), and dengue fever degree I (64.86%) with positive blue plasma lymphocytes (51.36%). Platelet counts, hemoglobin levels, hematocrit values, and leukocyte counts are significantly changed on days 3, 6, and 9, with probability values (p=0.000) less than p=0.01. The findings of the BNT test indicate that the number of platelets and haemoglobin on various days is significantly different (p<0.01), but the hematocrit value and leukocyte calculation are not significantly different (p>0.01). Conclusion: Clinical hematological tests and blood preparations reveal a blood component anomaly in Dengue Haemorragic Fever (DHF) patients at Bali Royal Hospital on days 3, 6, and 9.